A sustainable preparative-scale chemo-enzymatic synthesis of 6-hydroxy-5,7-dimethoxy-2-naphthoic acid (DMNA) from sinapic acid - Amandine L. Flourat; Nour Zeaiter; Erwan Vallée; V. P. Thinh Nguyen; Sami Fadlallah; Florent Allais (Green Chemistry Letters and Reviews, 2022)
Naturally occurring sinapic acid is a valuable synthon for many high-value applications (e.g. cosmetic, pharmaceutic) that can be found in numerous plants, especially Brasiccacea species (e.g. rapeseed, mustard). It has been demonstrated that alkaline extraction of matter rich in sinapic acid resulted in the conversion of sinapic acid into 6-hydroxy-5,7-dimethoxy-2-naphtanoic acid (DMNA). Although DMNA could be a potential alternative to petro-based naphtanoic acid used in polymers, untill now, no reliable (bio)synthetic procedure existed to synthesize it at the preparative-scale. Herein, starting from sinapic acid, we describe a very simple one-pot two-step chemo-enzymatic pathway to DMNA – and reaction intermediaries bislactone (BL) and thomasidioic acid (TA) – at gram scale using a simple filtration as purification step. Green metrics – Process Mass Index and EcoScale – have been determined to assess the sustainability of this new process. Finally, the antiradical activities of DMNA, BL and TA have been evaluated.